Religious Moderation In Islamic Boarding Schools: A Phenomenological Analysis of Socio-Cultural Practices and Classical Textual Foundations - Lubis, Mira Yanti; Hasibun, Sutan Botung; Nasution, Nur Hakima Akhirani; Wahyuni, Sri; Hakim, Rosniati (International Journal of Community Service (IJCS), 2025)
This article examines religious moderation (wasatiyyah) within Islamic boarding schools (pesantren) in Indonesia through a phenomenological analytical framework. Using qualitative research methodology, this study explores the lived experiences, socio-cultural practices, and engagement with classical Islamic texts (kitab kuning) that constitute religious moderation in pesantren environments. Drawing from in-depth interviews with 45 participants including pesantren leaders, educators (ustadz), and santri (students) across six pesantren institutions in East Java and Southeast Sulawesi, the research identifies three interconnected dimensions of religious moderation: theological foundations grounded in Qur'anic principles of wasatiyyah, socio-cultural practices manifesting tolerance and intercultural harmony, and pedagogical methods integrating classical Islamic scholarship with contemporary concerns. The findings demonstrate that religious moderation in pesantren operates as a comprehensive framework encompassing spiritual discipline, social ethics, and intellectual engagement, functioning simultaneously as a theological orientation, institutional practice, and educational outcome. The research contributes to contemporary discourse on Islamic education by providing evidence-based analysis of how traditional Islamic institutions operationalize moderation in pluralistic contexts, with implications for understanding pesantren's role in promoting social cohesion within Indonesia's diverse society.